2000
DOI: 10.7326/0003-4819-132-5-200003070-00006
|View full text |Cite
|
Sign up to set email alerts
|

Increased Susceptibility to Pulmonary Emphysema among HIV-Seropositive Smokers

Abstract: Infection with HIV accelerates the onset of smoking-induced emphysema. The results of this study support the emerging concept that cytotoxic lymphocytes may have an important role in emphysema pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
251
4
7

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(273 citation statements)
references
References 13 publications
8
251
4
7
Order By: Relevance
“…This organism has been reported to colonize 36% of lung tissues from patients with end-stage COPD versus 5% of specimens from healthy controls or those with less severe disease (Morris et al 2004). Smokers infected with Human Immuno-defi ciency Virus (HIV) also appear to have accelerated development of emphysema, particularly in those that also have high CD8 + lymphocyte counts in BAL fl uid (Diaz et al 2000). Pneumocystis colonization in lungs of rhesus macaques infected with Simian Immunodefi ciency Virus (SIV) generated CD8-lymphocyte and neutrophil predominant cellular inflammation in association with progressive airflow limitation and local increases in IL-8, IFN-γ, and TNF-α, reminiscent of the findings in emphysematous patients (Norris et al 2006).…”
Section: Microbial Peptide Antigensmentioning
confidence: 99%
“…This organism has been reported to colonize 36% of lung tissues from patients with end-stage COPD versus 5% of specimens from healthy controls or those with less severe disease (Morris et al 2004). Smokers infected with Human Immuno-defi ciency Virus (HIV) also appear to have accelerated development of emphysema, particularly in those that also have high CD8 + lymphocyte counts in BAL fl uid (Diaz et al 2000). Pneumocystis colonization in lungs of rhesus macaques infected with Simian Immunodefi ciency Virus (SIV) generated CD8-lymphocyte and neutrophil predominant cellular inflammation in association with progressive airflow limitation and local increases in IL-8, IFN-γ, and TNF-α, reminiscent of the findings in emphysematous patients (Norris et al 2006).…”
Section: Microbial Peptide Antigensmentioning
confidence: 99%
“…In addition to an increased risk for infectious pulmonary diseases, HIV-infected persons appear to have an increased risk for several noninfectious pulmonary conditions, including chronic obstructive pulmonary disease (COPD), lung cancer, and pulmonary arterial hypertension. HIV infection has been associated with several different manifestations of COPD and airway abnormalities, including features of emphysema (32), chronic bronchitis (33), nonspecific airway abnormalities, and bronchial hyperresponsiveness (34,35). In one study of 114 HIV-infected persons compared with 44 age-, sex-, and smoking-matched HIV-uninfected control subjects, 15% of the HIV-infected persons had emphysema on CT scan, compared with only 2% of non-HIV-infected persons (P 5 0.025) (32).…”
Section: Spectrum Of Hiv-associated Lung Infections and Complicationsmentioning
confidence: 99%
“…HIV infection has been associated with several different manifestations of COPD and airway abnormalities, including features of emphysema (32), chronic bronchitis (33), nonspecific airway abnormalities, and bronchial hyperresponsiveness (34,35). In one study of 114 HIV-infected persons compared with 44 age-, sex-, and smoking-matched HIV-uninfected control subjects, 15% of the HIV-infected persons had emphysema on CT scan, compared with only 2% of non-HIV-infected persons (P 5 0.025) (32). Another study found that HIV infection was associated with a 50 to 60% increased odds of COPD diagnosis (36).…”
Section: Spectrum Of Hiv-associated Lung Infections and Complicationsmentioning
confidence: 99%
“…[2][3][4] The progression of smoking-induced emphysema is hastened in individuals with HIV infection as well. 5 Increased rates of lung cancer among individuals living with HIV/AIDS appear to be attributed to smoking rather than immunosuppression. 6 Of the estimated 70% of cigarette smokers in the general adult U.S. population who reported visiting a physician or other health care professional at least once within the preceding 12 months, only 37% reported having received ad- vice from their health care provider to quit smoking.…”
Section: Introduction Imentioning
confidence: 99%